Metal–Organic Framework Materials. Edited by Leonard R. MacGillivray and Charles M. Lukehart. Issue 26 (1st June 2015) - Farrusseng, David
<x xml:space="preserve">Abstract</x> John Wiley and Sons, Hoboken, 2014. 592 pp., hardcover, € 175.00.—ISBN 978‐1119952893